Coprecipitation technique to prepare SrNb2O6 - Ravi, V (Materials Characterization, 2005)
A mixture of ammonium oxalate and ammonium hydroxide was used to co-precipitate strontium and niobium ions as strontium oxalate and niobium hydroxide under basic conditions. This precursor yielded SrNb2O6 ceramics on calcining at 650 degrees C. This is a much lower temperature compared to preparation of SrNb2O6 by the traditional solid state method (900 degrees C). Transmission electron microscopy (TEM) revealed that the average particle size is 100 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 550. The ferroelectric hysteresis loop parameters of these samples were also studied. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Ceramics; Electron microscopy; ferroelectric; Oxides; X-ray methods

Mixed-stack charge transfer crystals of pillar[5]quinone and tetrathiafulvalene exhibiting ferroelectric features - Shivakumar, Kilingaru I.; Swathi, Kadaba; Goudappagouda; Das, Tamal C.; Kumar, Ashwani; Makde, Ravindra D.; Vanka, Kumar; Narayan, Kavassery S.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemistry- A European Journal, 2017)
Ferroelectric materials find extensive applications in the fabrication of compact memory devices and ultra-sensitive multifunctional detectors. Face-to-face alternate stacking of electron donors and acceptors effectuate long-range unidirectional ordering of charge-transfer (CT) dipoles, promising tunable ferroelectricity. Herein we report a new TTF-quinone system-an emerald green CT complex consisting pillar[5]quinone (P5Q) and tetrathiafulvalene (TTF). The CT crystals, as determined by single crystal synchrotron X-ray diffraction, adopt a 1:1 mixed-stack arrangement of donor and acceptor with alternating dimers of TTF and 1,4-dioxane encapsulated P5Q. The TTF-P5Q.dioxane crystal possesses a macroscopic polarization axis giving rise to ferroelectricity at room temperature. The CT complex manifests ferroelectric features such as optical polarization rotation, temperature-dependent phase transition and piezoelectric response in single crystals. Ferroelectric behavior observed in P5Q-based CT complex widens the scope for further work on this structurally intriguing and readily accessible cyclic pentaquinone.
Keywords: Acceptor; Charge-transfer complexes; Chemistry; Conductors; DDQ; Donor; ferroelectric; Macrocycles; Organic Metals; Pi-interaction; Pillar[5]quinone; salts; Transfer Complexes; Transport

Influence of ionic radius on structural, optical and multiferroic properties of RMnO3 [R= Y, Er, Yb] hexamanganites - Inchara, D. R.; Singh, Kirandeep; Sangole, Mayur; Murari, M. S.; Daivajna, Mamatha D. (Physica B-Condensed Matter, 2025)
The crystalline samples of YMnO3, ErMnO3, and YbMnO3 were synthesized by a conventional solid-state reaction technique. The single-phase hexagonal structure with the P63cm space group was verified by X-ray diffraction (XRD) study. Morphological studies show that the grains are uniform and closely packed, and that the grain size increases as the ionic radii of the rare-earth ions decrease of rare earth ions and the samples are in the stoichiometry. From the Diffused Reflectance Spectroscopy study, narrow optical band gap is observed for all the samples. Magnetic phase transitions, corresponding to the antiferromagnetic ordering, were detected for all samples. The Neel temperature was found to increase with the decrease of the ionic radii of A site element in RMnO3 (Y, Er, and Yb) samples. Ferroelectric hysteresis loops at room temperature as a function of applied electric fields reveal the leaky behaviour. The dielectric constant and dielectric loss tangent variation across different frequencies are also explored for these samples. A summary and discussion of the structural, optical, magnetic and ferroelectric properties, underlying physical mechanisms, the role of the rare earth ions, and the complex interactions in hexagonal manganites, are presented in this paper. This work emphasizes how systematic variation of A-site ionic radii influences the multiferroic properties of RMnO3, gaining thorough insights into structure-property relationships that are essential to design multifunctional materials.
Keywords: Antiferromagnetic; ferroelectric; Multiferroics; Perovskites; Photovoltaic; Recombination centers